HUBUNGAN KEBIASAAN SARAPAN PAGI DENGAN STATUS GIZI PADA ANAK SEKOLAH DASAR NEGRI 171 PEKANBARU - Novita Lusiana (Ensiklopedia of Journal, 2020)
Breakfast or breakfast is the first food consumed by someone. Usually people eat dinner around 19:00 and only eat again in the morning around 06:00. Means that for about 10-12 hours they are fasting. With the existence of fasting, the supply of blood sugar (glucose) in a person's body is only enough for the activity of two to three hours in the morning. Without breakfast someone will experience hypoglycemia or below normal glucose levels. Hypoglycemia results in body trembling, dizziness and concentration pain. That's all because of lack of glucose which is a source of energy for the brain. This type of research is Observational Analytic Quantitative with Cross Sectional design. In this study the independent variables and the dependent variables are collected at the same time After conducting research on the Relationship of Nutritional Status with Breakfast Habits in Children at SDN 171 Pekanbaru in 2019 with a sample of 73 students, it was found that 73 children who normally had breakfast with thin nutritional status of 3 (33.3%) were not used 63 (98.4%), children who used to have breakfast with normal nutritional status were 3 (33.3%) while those who did not normally eat 1 (1.6%), while children who usually had breakfast with fat nutritional status were 3 ( 33.3%) unusual breakfast breakfast 0 (0.0%). As an educational institution SDN 171 Pekanbaru can provide information about the relationship of nutritional status with the habit of having breakfast in children using the media leaflets, brochures and others.